2021
DOI: 10.1503/jpn.200010
|View full text |Cite
|
Sign up to set email alerts
|

Fatty acid amide hydrolase binding is inversely correlated with amygdalar functional connectivity: a combined positron emission tomography and magnetic resonance imaging study in healthy individuals

Abstract: Background: Upregulation of the endocannabinoid enzyme fatty acid amide hydrolase (FAAH) has been linked to abnormal activity in frontoamygdalar circuits, a hallmark of posttraumatic stress disorder. We tested the hypothesis that FAAH levels in the amygdala were negatively correlated with functional connectivity between the amygdala and prefrontal cortex, subserving stress and affect control. Methods: Thirty-one healthy participants completed positron emission tomography (PET) imaging with the FAAH probe [C-11… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
11
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 53 publications
3
11
1
Order By: Relevance
“…In adults, converging evidence across species has observed lower anxiety symptoms and greater resting‐state fronto‐amygdala connectivity in carriers of the A‐allele variant, relative to non‐carriers (Dincheva et al., 2015; Gärtner et al., 2019). Furthermore, recent work found that the strength of fronto‐amygdala connectivity was inversely correlated with amygdalar binding of a FAAH probe, although this study did not find evidence for a relationship between fronto‐amygdala connectivity and the FAAH C385A polymorphism (Green et al, 2021). Other studies have identified A‐allele carriers as having lower threat‐related amygdala reactivity (Hariri et al., 2009), as well as faster amygdala habituation to threat (Gunduz‐Cinar et al., 2013).…”
Section: Introductioncontrasting
confidence: 72%
“…In adults, converging evidence across species has observed lower anxiety symptoms and greater resting‐state fronto‐amygdala connectivity in carriers of the A‐allele variant, relative to non‐carriers (Dincheva et al., 2015; Gärtner et al., 2019). Furthermore, recent work found that the strength of fronto‐amygdala connectivity was inversely correlated with amygdalar binding of a FAAH probe, although this study did not find evidence for a relationship between fronto‐amygdala connectivity and the FAAH C385A polymorphism (Green et al, 2021). Other studies have identified A‐allele carriers as having lower threat‐related amygdala reactivity (Hariri et al., 2009), as well as faster amygdala habituation to threat (Gunduz‐Cinar et al., 2013).…”
Section: Introductioncontrasting
confidence: 72%
“…Interestingly, administering a FAAH inhibitor is not the only way to examine the effects of elevated AEA on fear conditioning processes - there is also a fairly common functional single nucleotide polymorphism (SNP) in the FAAH gene (C385A; rs324420) that results in lower levels of FAAH protein, and as a result, increased AEA concentrations ( Mayo et al, 2020a , Sipe et al, 2002 , Spagnolo et al, 2016 ). Interestingly, individuals that possess the FAAH C385C → A mutation exhibit elevated AEA concentrations (due to lower FAAH expression) in the amygdala and enhanced fear extinction recall neurocircuitry (i.e., enhanced regulation of amygdala by ventromedial prefrontal cortex; vmPFC), which is in contrast to women with PTSD who typically exhibit altered fear extinction neurocircuitry (e.g., amygdala hyperreactivity, vmPFC and hippocampal hyporeactivity) and poor extinction learning ( Mayo et al, 2021 , Mayo et al, 2020a , Green et al, 2021 ). Similar to FAAH inhibition, in addition to accelerated fear extinction learning ( Dincheva et al, 2015 ), elevated AEA due to this genetic polymorphism has also been linked to decreased anxiety responses following the presentation of stress- and threat-inducing stimuli ( Hariri et al, 2009 ) in healthy humans without a clinical anxiety disorder, and lower hyperarousal symptoms in adults with PTSD ( Spagnolo et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…There are very few studies that have explored in vivo measures of personality functioning in ASPD or BPD and none to our knowledge that have specifically assayed components of the ECS, apart from one functional MRI study of healthy individuals that found no relationship between neuroticism and amygdala [ 11 C]CURB λ k 3 35 . Here, we focused on the relationship between FAAH binding and neuroticism in personality disorders.…”
Section: Discussionmentioning
confidence: 99%